Study on aspirin-induced bronchial obstruction in children with bronchial asthma - Saraçlar, Yıldız; Tuncer, Ayfer (The Turkish Journal of Pediatrics, 1981)
It is well known that aspirin may cause bronchial obstruction. It is generally assumed that aspirin-induced bronchial obstruction starts at a subclinical level and develops severe symptoms at older ages. It is possible to demonstrate asymptomatic bronchial obstruction by spirometric studies. Only a few reports concerning this matter in children have been published. In order to detect bronchial obstruction due to aspirin, pulmonary function tests were applied to fifty-two children with mild to moderate asthma. The results indicated 14% intolerance and were compared with those in the literature.